"All that we see is seen in perspective": point of view as word and image. Issue 3 (3rd July 2021) - Park, Julie
Abstract: Whereas the fictiveness of narrative perspective is taken for granted in literature, it also emerges as a salient element in the experiences of pictorial art and architecture as part of a viewer's internal response to their altered views of reality. Whether a visual technique or a narrative one for shaping the way things are seen, perspective assumes that the conditions of seeing an object are flexible and open to mental and material variables in diverse historical media and sites. These range from the cognitively provocative trompe l'œil fresco paintings of seventeenth-century Italy, the typographical headings used as chapter divisions in eighteenth-century British novels, and hand-colored eighteenth-century prints of city scenes made to look three-dimensional through an optical device, to the inscribed stones used in post war Berlin monuments, and an art historian's recent perspectives on memories of his twentieth-century childhood home. Concentrating on perspective foremost as a medium and conduit for the imagination, Getting Perspective reveals its transhistorical role in word and image as a shaper and maker of imagined worlds.